Key technologies and solutions of VR based on IPTV - Feng LI; Chen YANG; Xingda LI (Dianxin kexue)
As a new technology,virtual reality technology’s innovation on video brings users a completely new interactive experience.The developments in VR/AR industry at home and abroad were introduced.The IPTV-based demand of the VR was analyzed.Furthermore,the key technologies including video codec,projections,integrated service platform techniques,set top box,network transmission were also researched.At last,a solution and a process were presented from two different scenes.It’s also a solution for reference to the development of IPTV VR.